Gluten-free diet intervention reduces thiamine intake in two weeks, increases glycaemic response and decreases body weight in four weeks, with no long term nutritional deficiencies. (3rd April 2022) - Goddard, Lucy; Begovich, Lina; Tokic, Iva; Clegg, Miriam E.; Thondre, Pariyarath Sangeetha
Abstract: This research investigated the effects of gluten free diet (GFD) on nutritional intake, glycaemic and insulin response. In a cross-sectional study, participants who consumed gluten-containing diet (GCD; n  = 11) and GFD ( n  = 11) completed a food diary, blood glucose and insulin measurements. In a pre-post intervention study ( n  = 11), glycaemic and insulin responses were tested before and after four weeks of a GFD. Food intake was recorded before and after two weeks. No significant differences in nutrient intake, glycaemic or insulin responses were found in the cross-sectional study. In the intervention study, there was a significant reduction in body weight ( p  = .007) and body mass index (BMI) ( p  = .004) after four weeks and lower thiamine intake ( p  = .021) after two weeks of GFD. Glycaemic response was significantly higher ( p  < .05) following GFD with no differences in insulin response. These differences were not evident if GFD was followed for a longer period, possibly due to improved food choices.